Pelatihan Arduino Untuk Pembuatan Alat Ukur Suhu Tubuh Non Kontak Berbasis Android Pada Siswa SMA - Sultan; I Made Ginarsa; Agung Budi Muljono; I Made Ari Nrartha; Sudi Mariyanto Al Sasongko (Universitas Mataram, 2022)
SMAN 3 Mataram has a vision of forming human resources who are honest, trustworthy, and smart. One of the missions is to improve the ability in science, technology and skills. During the COVID-19 pandemic, healthy and clean living behavior is required according to the protocol by keeping a distance and avoiding crowds. To encourage skill and creative students, the PKM Team carries out Arduino training to measure non-contact body temperature. Arduino training modules are made easy to disassemble and can be monitored by Android phones via Bluetooth, with the MIT APP Inventor 2 program interface. The MLX90614 sensor can be used as a body temperature measurement via wireless during the Covid-19 pandemic. The training was carried out by means of presentations on the basic principles of Arduino and the introduction of analog sensors to measure body temperature. In order to be effective and efficient, the presentation of hardware circuits is directly practiced and supervised by electrical students. Competent lecturers provide training on making android programs, case studies of body temperature sensors. This PKM activity was attended by 23 students who were divided into 4 groups to match the number of modules. Based on the results of the evaluation of the pretest and posttest, there was an increase in knowledge of 34.5% from the pretest average of 51.2 to the posttest average of 78.2. A total of 13 students (56.6%) had additional motivation to find out more about the Arduino application.